5(7+8x)+11=

Simple and best practice solution for 5(7+8x)+11= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7+8x)+11= equation:


Simplifying
5(7 + 8x) + 11 = 0
(7 * 5 + 8x * 5) + 11 = 0
(35 + 40x) + 11 = 0

Reorder the terms:
35 + 11 + 40x = 0

Combine like terms: 35 + 11 = 46
46 + 40x = 0

Solving
46 + 40x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-46' to each side of the equation.
46 + -46 + 40x = 0 + -46

Combine like terms: 46 + -46 = 0
0 + 40x = 0 + -46
40x = 0 + -46

Combine like terms: 0 + -46 = -46
40x = -46

Divide each side by '40'.
x = -1.15

Simplifying
x = -1.15

See similar equations:

| 15+x=3x-15 | | -5(a-1)=-35 | | 2x^4+22x^2-15x+7=0 | | 4=32/? | | 17=2-4K | | 9x-22=-8+2x | | 3x-8+4+5x-2x=x-3+2x-1-9 | | -8=w+5w-10w-20 | | 4x+6=2x+15 | | 20x+5y-20=21x+4 | | -2(6a-7)=31-5a | | 4a+b=22 | | 3x^3y^3/x^2y | | 3x/5=2x/3=1 | | f(x)=(x^2-4x+6)-4 | | -7f+3-4=30 | | 3n-5=-8-10n-6(6+5n)-4 | | 2x6x6x6/(4x-4) | | 9n-13=5 | | -32=72 | | 5.37/0.001 | | -13=-16+9k | | 195=(x*16) | | 4(x+7)(x+7)=11 | | 93=4x+7(3x-5)+3 | | 37/8-15/8 | | 9t+7=25 | | [2h-1]=5 | | 9t^1/2-4 | | .5-x/5=-2/5 | | 2.49=0.49+16 | | 11.4=4x-3 |

Equations solver categories